2018
DOI: 10.24326/asphc.2018.4.8
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF EXOGENOUS SALICYLIC ACID ON THE RESPONSE OF SNAP BEAN (Phaseolus vulgaris L.) AND JERUSALEM ARTICHOKE (Helianthus tuberosus L.) TO DROUGHT STRESS

Abstract: Water shortage is a major problem that limits growth and productivity of plants in arid and semi-arid regions. Protecting plants from adverse environmental conditions by using simple methods could be of great value under these conditions. In the present study, we examined water status and drought tolerance of snap bean, a drought-sensitive plant, and Jerusalem artichoke, a relatively drought tolerant plant in response to the application of salicylic acid (SA). Different levels of SA were applied and several ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Salicylic acid (SA) in appropriate concentrations considered as a good factor to control biotic and abiotic stresses in plants (28). Many studies showed that SA is used as a plant growth regulator to mitigate the harmful effects of drought (26). It improves Plant growth, enzyme activity, ions absorption and movement in plant (66) study showed that foliar spraying with SA and tryptophan had an effective role in reducing the negative effects on corn plants exposed to drought.…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid (SA) in appropriate concentrations considered as a good factor to control biotic and abiotic stresses in plants (28). Many studies showed that SA is used as a plant growth regulator to mitigate the harmful effects of drought (26). It improves Plant growth, enzyme activity, ions absorption and movement in plant (66) study showed that foliar spraying with SA and tryptophan had an effective role in reducing the negative effects on corn plants exposed to drought.…”
Section: Introductionmentioning
confidence: 99%